2019
DOI: 10.3354/dao03416
|View full text |Cite
|
Sign up to set email alerts
|

Podocotyle atomon (Trematoda: Digenea) impacts reproductive behaviour, survival and physiology in Gammarus zaddachi (Amphipoda)

Abstract: 19The Trematoda are a group of phylogenetically diverse metazoan parasites that 20 exhibit complex life cycles that often pass through invertebrate and vertebrate hosts. 21Some trematodes influence their host's behaviour to benefit transmission. Their 22 parasitic influence may impact host population size by inhibiting an individual's 23 reproductive capacity. 24We assessed the impact of infection by Podocotyle atomon on the reproductive 25 behaviour and fecundity of its amphipod intermediate host, Gammarus za… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Generally, parasite prevalence in aquatic organisms, including amphipods, is positively correlated with host size, as older individuals are more likely to be exposed to infections over their lifespan (Poulin, 2000;Prati et al, 2023;Soldánová et al, 2010). Furthermore, size-asymmetric cannibalism, which is common in many aquatic taxa, including G. pulex, may potentially favor the transmission of parasites via ingestion of infected individuals (Arundell et al, 2019a(Arundell et al, , 2019bMacNeil et al, 2003;McGrath et al, 2007).…”
Section: Prevalence Of Metacollinia Emscheri N Spmentioning
confidence: 99%
“…Generally, parasite prevalence in aquatic organisms, including amphipods, is positively correlated with host size, as older individuals are more likely to be exposed to infections over their lifespan (Poulin, 2000;Prati et al, 2023;Soldánová et al, 2010). Furthermore, size-asymmetric cannibalism, which is common in many aquatic taxa, including G. pulex, may potentially favor the transmission of parasites via ingestion of infected individuals (Arundell et al, 2019a(Arundell et al, , 2019bMacNeil et al, 2003;McGrath et al, 2007).…”
Section: Prevalence Of Metacollinia Emscheri N Spmentioning
confidence: 99%
“…2b). Visual identification of infection was deemed acceptable as it had previously been shown that 84.2% of animals with one or more visible cysts were PCR-positive for P. atomon infection and only one of 58 individuals with no visible cysts was PCR-positive (1.7%) (K. Arundell et al 2019).…”
Section: The Relationship Between Fa and Trematode Infection In Gammamentioning
confidence: 99%